Sharia, Gender, and Science in the Construction of ‘Iddah: The Response of Banyumas' Ulamas - Juliansyahzen, Muhammad Iqbal; Fadhilah, Eva; Syufaat, Syufaat; Zahro, Anisatuz (El-Mashlahah, 2024)
The development of science necessitates changes in various issues of human life, including matters of family law. One of the family law issues that often sparks debate is the issue of 'iddah. One of the reasons (reason) often found in the discussions of scholars is to ensure the cleanliness of the uterus from the fetus. If this argument is used as the main basis, it is refuted by the development of medical technology, which can ensure the cleanliness of the uterus in a relatively short time. Likewise, from a gender perspective, because the owner of the womb is only a woman, it cannot be exchanged. This study aims to analyze the extent to which Banyumas’ Ulama views respond to the development of science and gender discourse in the context of family law. This research is empirical legal research, analyzing the responses of Banyumas scholars. Researchers collected data from scholars who came from different religious organization backgrounds, namely Nahdlatul Ulama, Muhammadiyah, and al-Irsyad. These three are the organizations with the most followers in Banyumas. Banyumas became the locus of this research because there is a view that egalitarian principles are living values in society, as described in the chronicle historical texts (babad). The study concluded that the responses of the Banyumas Ulama were divided into two groups, namely textualists and semi-textualists. However, the semi-textualist group is more dominant among them. This research at the same time proves that the relationship between religion and science has not yet reached an integrative or even transdisciplinary level but is still at a dialogic level, and there is even a dualistic view.